Analisis Strategi Kewirausahaan Kedai Kopi Jivanam Dalam Meningkatkan Daya Saing Di Era Ekonomi Kreatif - Dzikry, Afdal; Maulana, Abdul Galang; Muh. Faldi; Vitria, Nining; Junianto, Ferdiansyah Dwi Cahyo; Halim, Rahmawati (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This study aims to analyze the entrepreneurial strategies implemented by Kedai Kopi Jivanam in an effort to increase business competitiveness in the creative economy era. The method used in this study is a qualitative approach with a descriptive research type. Data collection was conducted through in-depth interviews with the business owner as the main informant. The results of the study indicate that Kedai Kopi Jivanam developed an entrepreneurial strategy that emphasizes creating customer experiences through personal interactions between baristas and consumers, innovative and sustainable product development, and the use of social media as a promotional medium and community building. Amidst the challenges of fluctuating world coffee prices, Kedai Kopi Jivanam remains able to maintain product quality and maintain customer loyalty by optimizing the role of creative human resources and conducting data-based business evaluations. Thus, the implemented entrepreneurial strategy has been proven to contribute to increasing Kedai Kopi Jivanam's competitiveness amidst the increasingly competitive coffee shop industry.